The THE EFFECT OF HEALTH EDUCATION ON ABILITY LEVELS IN BURN FIRST AID IN AL-LATHIFAH ISLAMIC BOARDING SCHOOL: THE EFFECT OF HEALTH EDUCATION ON ABILITY LEVELS IN BURN FIRST AID IN AL-LATHIFAH ISLAMIC BOARDING SCHOOL - Safitry, Andres; Jainurakhma, Janes; Muhammad, Zulfikar (WELL BEING, 2020)
Burns can occur due to negligence in everyday life or an accident both at home, industry and even due to mass accidents. With so many people still making mistakes or don't know how to do first aid right. The purpose of this study was to determine whether there was an effect of health education using simulation methods with booklet media on the ability of students to provide first aid to burn victims at Al-Lathifah Islamic Boarding School. This type of research uses experimental research designs with one group pretest-posttest design approach. The sampling technique uses purposive sampling with a sample of 35 respondents. The research instrument used observation sheets which were then analyzed by the Wilcoxon test. From the research results, the mean at pre-test is 1.63 and after the post-test is increased, the mean is 13.66. Based on the Wilcoxon test, a significant P-value of <0.001 is obtained, which can be interpreted as influencing before and after health education is given. With the majority of respondents who were teenagers, health education using simulation methods with a media booklet for 60 minutes was able to influence the level of ability in first aid burns. Giving first aid skills to the right burn victims in the Islamic boarding school environment is very much needed, to prevent defects in the integrity of the skin due to burns.